Analisis Pengaruh Profitabilitas, Ukuran Perusahaan, Kebijakan Deviden Dan Keputusan Investasi Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan LQ45 Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2014) - Sugiarti, Dani; , Dr. Anton Agus Setyawan, SE., M.Si (2015)
Companies with business it does aim to maximize the wealth of shareholders which will be reflected in the value of the company. The company's value is the price paid by the prospective buyer if the company is sold. The purpose of this study was to examine the effect of retrun on equity (ROE), the size of the company, the dividend payout ratio (DPR) and price earnings ratio (PER) of the firm value at LQ45 companies that listed on the Indonesia Stock Exchange. The population used in this study are all LQ45 companies listed on the Indonesia Stock Exchange. The sampling method with a purposive sampling in accordance with the specified criteria. The number of samples collected as many as 18 companies with 72 data. The collected data were analyzed using panel data analysis models using Eviews Fixed Effect 7. Based on the results in regression models in mind a few things, as follows: (1) variable retrun on equity (ROE) has positive and statistically significant to the firm value, ( 2) variable firm size negative and statistically significant to firm value (3) a variable dividend payout ratio (DPR) has positive and statistically not significant to the firm value, (4) a variable price earnings ratio (PER) has positive and statistically significantly to the firm value . Keywords: return on equity (ROE), firm size, dividend payout ratio (DPR) and price earnings ratio (PER), firm value